Clinical Comparative Study Of Post-operative Sensitivity Between Giomer And Nano Hybrid Composite - عبدالله, عاطف; الغدا, عنان (Latakia University Journal -Medical Sciences Series, 2020)
Objective: This clinical study aims to evaluate the postoperative sensitivity in class I restorations when restored with either Nano hybrid composite or Giomer. Materials and Methods: The research sample consisted of 15 patients; each patient has two molars at least which have type I caries. This sample was divided into two groups, molars restored with Composite (group 1) and molars restored with Giomer (group 2), whether was upper or lower. Class I cavity was prepared with a specific dimensions on the occlusal surface only, group 1 cavities restored with Nano hybrid composite (Tetric Evo Ceram, Ivoclar Vivadent, Ellwangen, Germany) while the second set (group 2) restored with Giomer (Beautifil II, Shofu, Japan), post-operative sensitivity was evaluated for 3 days, 7 days, 3 weeks, 7 weeks according to Visual Analogue Scale (VAS). Results: There was no statistical difference between Beautifil II and Tetric Evo Ceram for post-operative sensitivity in all observation periods.